Cyclic Permutations in Determining Crossing Numbers - Klešč Marián; Staš Michal (Discussiones Mathematicae Graph Theory, 2022)
The crossing number of a graph G is the minimum number of edge crossings over all drawings of G in the plane. Recently, the crossing numbers of join products of two graphs have been studied. In the paper, we extend know results concerning crossing numbers of join products of small graphs with discrete graphs. The crossing number of the join product G*+ Dn for the disconnected graph G* consisting of five vertices and of three edges incident with the same vertex is given. Up to now, the crossing numbers of G + Dn were done only for connected graphs G. In the paper also the crossing numbers of G*+ Pn and G* + Cn are given. The paper concludes by giving the crossing numbers of the graphs H + Dn, H + Pn, and H + Cn for four different graphs H with |E(H)| ≤ |V (H)|. The methods used in the paper are new. They are based on combinatorial properties of cyclic permutations.